Pengaruh Nilai-Nilai Islami dan Self-Learning Ability terhadap Kesiapan Generasi Z Memasuki Dunia Kerja di Desa Cipenjo - Ani Nuraeni; Mutdi Ismuni; Supriatal Supriatal (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of Islamic Values and Self-learning ability on the Readiness of Generation Z to Enter the World of Work in Cipenjo Village. This study uses a quantitative method with probability sampling technique through the simple random sampling method. Data processing and statistical analysis were carried out using SPSS software version 25. The results of the study showed that Islamic values and Self-learning ability simultaneously had a positive and significant effect on the readiness of Generation Z to Enter the World of Work in Cipenjo Village with an Adjusted R Square value of 0.577 or 57.7%, while 42.3% the rest are influenced by other variables outside of the study. Partially, Islamic values have a positive and significant effect on Generation Z's readiness to enter the world of work. Similarly, Self-learning ability has a positive and significant effect on Generation Z's Readiness to Enter the World of Work. The findings of this study show that the application of good Islamic values and high independent learning skills can increase the readiness of Generation Z in facing the world of work. This research is expected to contribute to the development of human resources, especially in increasing the work readiness of Generation Z in Cipenjo Village